Knowledge, attitudes and practices on prevention and control of high-consequence infectious diseases and critical care among intensive care personnel in Rwanda: a cross-sectional survey - L. Schneider; M. Umutoni; V. Ndagijimana; M. Abdelrhman; T. Cronen; M. Nkeshimana; P. Banguti; C. Karamira; E. Seruyange; T. Piening; A. Phuti; T. Paerisch; et al. (Infection Prevention in Practice)
Summary: Introduction: Intensive care personnel in countries prone to outbreaks of high-consequence infectious diseases (HCIDs), such as Ebola virus disease, stand at the forefront of caring for affected patients. This study describes the knowledge, attitudes and practices (KAP) of intensive care personnel in Rwanda on the management and infection prevention and control (IPC) of HCIDs. Methods: A cross-sectional survey was carried out among staff working in the 4 operational intensive care units in September 2022. The self-administered questionnaire collected information on participants' background and their KAP on critical care (CC), HCIDs and IPC. Results: Of the 107 participants, 67 (62.6%) had less than 4 years' work experience in CC. 41 (38.3%) of them had attended trainings on IPC since 2020. In univariate analyses, a higher knowledge score was associated with being a physician, years of working in CC and differed by hospital. A large proportion perceived their knowledge on CC as good or very good (58.0%) and their everyday risk of acquiring an infection as at least high (48.6%). Overall, 72.9% reported compliance with hand hygiene measures. However, around a quarter of participants reported rarely or never avoiding recapping of needles or never or rarely taking additional precautions during aerosol-generating procedures. Conclusions: Staff had a moderate knowledge base and might benefit from continuous learning on CC and HCIDs. The perception of high risk of infection at work stands in contrast with lack of compliance with basic IPC practices which should be reinforced to avoid preventable and potentially fatal infections.